Decorative layer and preparation method thereof, automotive interior trim part and vehicle

By using multi-stage structural carbon nanotube materials in the automotive decorative layer, the problems of the decorative layer in microbial growth and electromagnetic interference are solved, and the comprehensive performance improvement of flame retardant, antibacterial and electromagnetic wave absorption is achieved.

CN119777147APending Publication Date: 2025-04-08BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411655558.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The automotive decorative layer is easily a breeding ground for microorganisms to breed and reproduce during use, and there are shortcomings in issues such as electromagnetic interference and flammability of polymer materials.

Method used

Multi-stage structural carbon nanotube material is used as the cladding layer, including carbon nanotubes, Schiff alkali polymer layer coated on the surface of the carbon nanotubes, and metal particles supported on the Schiff alkali polymer layer, absorb electromagnetic waves through highly conductive materials and reduce combustion risks through flame retardant materials.

Benefits of technology

The decorative layer has achieved good flame retardancy, antibacteriality and electromagnetic wave absorption performance, ensuring that the vehicle is lightweight while improving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119777147A_ABST
    Figure CN119777147A_ABST
Patent Text Reader

Abstract

The invention provides a decorative layer and a preparation method thereof, an automobile interior trim part and a vehicle, and belongs to the technical field of automobile parts, the decorative layer is applied to the vehicle and comprises a base material layer and a coating layer, and the coating layer coats the base material layer. The coating layer comprises a multilevel structure carbon nanotube material, and the multilevel structure carbon nanotube material comprises a carbon nanotube, a Schiff base polymer layer coating the surface of the carbon nanotube, and metal particles loaded on the Schiff base polymer layer. The decorative layer provided by the embodiment of the invention has flame retardance, antibacterial property and electromagnetic wave absorption capacity, and after the decorative layer is applied to the vehicle, the safety can be improved while the light weight of the vehicle can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of vehicle parts, and in particular to a decorative layer and a preparation method thereof, an automobile interior decoration part, and a vehicle. Background Art

[0002] The decorative layer of the car is widely used in the interior and exterior decoration of the vehicle, and has the characteristics of lightweight. However, the temperature, humidity and surface nutrients of the car decorative layer during use provide a suitable growth environment for microorganisms, making the car decorative layer a hotbed for the growth and reproduction of microorganisms such as bacteria and fungi. In addition, with the development of electrification and intelligence of automotive electronics, electromagnetic interference and flammable polymer materials have also become one of the problems that cannot be ignored in the cabin. However, in the relevant technology, the research on the decorative layer is mainly in the flame retardant and antibacterial properties, and there is less research on the electromagnetic wave absorption performance. Summary of the invention

[0003] The embodiments of the present application provide a decorative layer and a preparation method thereof, an automotive interior trim, and a vehicle. The decorative layer has good flame retardancy and antibacterial properties, and also has electromagnetic wave absorption performance, which can ensure the lightweight of the vehicle while improving safety.

[0004] In order to achieve the above object, according to a first aspect of the present application, a decorative layer is provided, which is applied to a vehicle, and includes:

[0005] substrate layer;

[0006] The coating layer covers the base material layer;

[0007] The coating layer includes a multi-level structure carbon nanotube material, which includes carbon nanotubes, a Schiff base polymer layer coated on the surface of the carbon nanotubes, and metal particles supported on the Schiff base polymer layer.

[0008] Optionally, the metal particles include silver particles.

[0009] Optionally, the Schiff base polymer in the Schiff base polymer layer is formed by polymerizing an amine group-containing compound and an aldehyde group-containing compound.

[0010] Optionally, the structural formula of the amine-containing compound is as shown in Formula I to Formula III:

[0011]

[0012] Optionally, the structural formula of the compound containing an aldehyde group is as shown in Formula IV-Formula VI:

[0013]

[0014] Optionally, the carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0015] Optionally, the base layer includes a fabric layer, and the covering layer covers the fabric layer.

[0016] According to a second aspect of the present application, a method for preparing a decorative layer is also provided, which is used to prepare the decorative layer as described above, comprising:

[0017] Providing multi-level structured carbon nanotube materials;

[0018] Dispersing the multi-level structure carbon nanotube material into the polymer solution to obtain a multi-level structure carbon nanotube material solution;

[0019] The multi-level structure carbon nanotube material solution is coated on the substrate layer and dried to obtain a decorative layer.

[0020] Optionally, the polymer solution includes at least one of a chitosan solution, a sodium alginate solution and a polyvinyl alcohol solution.

[0021] Optionally, the mass proportion of the multi-level structure carbon nanotube material in the multi-level structure carbon nanotube material solution is 5%-30%.

[0022] Optionally, the concentration of chitosan in the chitosan solution is 1 mg / mL-20 mg / mL;

[0023] and / or, the concentration of sodium alginate in the sodium alginate solution is 1 mg / mL-20 mg / mL;

[0024] And / or, the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 1 mg / mL-20 mg / mL.

[0025] Optionally, a method for preparing a multi-level structured carbon nanotube material comprises:

[0026] dispersing carbon nanotubes in a first solvent to obtain a carbon nanotube solution;

[0027] Adding a first solution to the carbon nanotube solution and reacting the solution to obtain a first mixed solution; wherein the first solution includes an amine-containing compound;

[0028] Adding a second solution to the first mixed solution and reacting the solution to obtain a second mixed solution; wherein the second solution includes a compound containing an aldehyde group;

[0029] performing solid-liquid separation on the second mixed solution to obtain coated carbon nanotubes, and redispersing the coated carbon nanotubes in a second solvent to obtain a coated carbon nanotube solution;

[0030] adding a silver nitrate solution to the coated carbon nanotube solution to obtain a third mixed solution;

[0031] adding a reducing agent solution to the third mixed solution and reacting the mixture to obtain a fourth mixed solution;

[0032] The fourth mixed solution is subjected to solid-liquid separation and dried to obtain a multi-level structure carbon nanotube material.

[0033] Optionally, in the carbon nanotube solution, the concentration of carbon nanotubes is 0.1 mg / mL-20 mg / mL;

[0034] and / or, in the first solution, the concentration of the amine-containing compound is 1 mg / mL-20 mg / mL;

[0035] And / or, in the second solution, the concentration of the aldehyde group-containing compound is 1 mg / mL-20 mg / mL.

[0036] Optionally, the first solvent comprises at least one of ethanol and methanol;

[0037] And / or, the second solvent includes at least one of ethanol and methanol.

[0038] Optionally, in the silver nitrate solution, the concentration of silver nitrate is 1 mg / mL-20 mg / mL.

[0039] Optionally, the reducing agent solution includes at least one of a sodium borohydride solution and a sodium citrate solution.

[0040] According to a third aspect of the present application, there is also provided an automobile interior trim part, comprising the decorative layer as described above, and / or a decorative layer prepared by the method for preparing the decorative layer as described above.

[0041] According to a fourth aspect of the present application, a vehicle is also provided, comprising the automobile interior component as described above.

[0042] The decorative layer provided in the embodiment of the present application is applied to vehicles. The decorative layer includes a substrate layer and a coating layer, and the coating layer is coated on the substrate layer. The coating layer includes a multi-level structure carbon nanotube material, and the multi-level structure carbon nanotube material includes carbon nanotubes, a Schiff base polymer layer coated on the surface of the carbon nanotubes, and metal particles loaded on the Schiff base polymer layer. Among them, the carbon nanotubes and the metal particles are both highly conductive materials. When electromagnetic waves interact with the carbon nanotubes and the metal particles, the high conductivity of the carbon nanotubes and the metal particles can cause the electromagnetic waves to generate current on their surface and inside, and then convert them into other forms of energy to achieve the absorption of electromagnetic waves. The carbon nanotubes and the metal particles work synergistically with each other, which can significantly improve the electromagnetic wave absorption performance. The Schiff base polymer layer coated on the surface of the carbon nanotubes has a carbon-nitrogen double bond, which can interact with the components on the bacterial cell wall or cell membrane, thereby having good antibacterial properties. The Schiff base polymer in the Schiff base polymer layer can undergo a cross-linking reaction at high temperature to form a stable carbon layer, thereby effectively isolating the transfer of heat and oxygen to achieve a flame retardant effect. The Schiff base polymer can also release non-combustible gases such as water vapor and carbon dioxide during combustion to reduce the speed of the combustion reaction. Therefore, the decorative layer provided in the embodiment of the present application has flame retardancy, antibacterial properties and electromagnetic wave absorption capabilities. When applied to a vehicle, it can ensure that the vehicle is lightweight while improving safety.

[0043] Other features and advantages of the present application will be described in detail in the subsequent detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0045] In order to more completely understand the present application and its beneficial effects, the following description will be given in conjunction with the accompanying drawings, wherein the same figure numbers represent the same parts in the following description.

[0046] Figure 1 is an XRD spectrum analysis diagram of the multi-level structure carbon nanotube provided in Example 1 of the present application;

[0047] Figure 2 It is a transmission electron microscope and energy dispersive X-ray spectroscopy analysis diagram of the carbon nanotubes, coated carbon nanotubes, and multi-level structure carbon nanotube materials provided in the examples of the present application. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0049] In the first aspect, the embodiment of the present application provides a decorative layer for use in vehicles. The decorative layer includes a substrate layer and a coating layer, and the coating layer is coated on the substrate layer. The coating layer includes a multi-level structure carbon nanotube material, and the multi-level structure carbon nanotube material includes carbon nanotubes, a Schiff base polymer layer coated on the surface of the carbon nanotubes, and metal particles loaded on the Schiff base polymer layer. Among them, the carbon nanotubes and the metal particles are both highly conductive materials. When electromagnetic waves interact with the carbon nanotubes and the metal particles, the high conductivity of the carbon nanotubes and the metal particles can cause the electromagnetic waves to generate current on their surface and inside, and then convert them into other forms of energy to achieve the absorption of electromagnetic waves, and the carbon nanotubes and the metal particles work synergistically with each other, which can significantly improve the electromagnetic wave absorption performance. The Schiff base polymer layer coated on the surface of the carbon nanotubes has a carbon-nitrogen double bond, which can interact with the components on the bacterial cell wall or cell membrane, thereby having good antibacterial properties. The Schiff base polymer in the Schiff base polymer layer can undergo a cross-linking reaction at high temperature to form a stable carbon layer, thereby effectively isolating the transfer of heat and oxygen to achieve a flame retardant effect. The Schiff base polymer can also release non-combustible gases such as water vapor and carbon dioxide during combustion to reduce the speed of the combustion reaction. Therefore, the decorative layer provided in the embodiment of the present application has flame retardancy, antibacterial properties and electromagnetic wave absorption capabilities. When applied to a vehicle, it can ensure that the vehicle is lightweight while improving safety.

[0050] In addition to the above-mentioned multi-level structure carbon nanotube materials, the carbon nanotubes, Schiff base coating layers or silver particles in the multi-level structure carbon nanotube materials can also be replaced to form a composite material with corresponding functions. For example, the Schiff base polymer layer can be replaced, such as by a nitrogen heterocyclic compound with stronger coordination ability, or by introducing fluorine or silicon elements with low surface energy to improve hydrophobicity, or by introducing phosphorus elements to enhance flame retardancy, etc. The carbon nanotubes can be replaced by boron nitride with good thermal conductivity, graphene with good electrical conductivity, or gold nanoparticles with good light energy performance.

[0051] In some embodiments, the metal particles include silver particles. Silver particles have good electrical conductivity, so that the silver particles and carbon nanotubes work together to produce better electromagnetic wave absorption performance. Silver particles can also release silver ions to combine with negative charges on bacterial cell walls, destroying the cell structure of bacteria and causing bacterial death, thereby improving antibacterial performance.

[0052] In addition, the metal particles may further include at least one of copper particles, iron particles, cobalt particles, and nickel particles.

[0053] In some embodiments, the Schiff base polymer in the Schiff base polymer layer is formed by polymerizing an amine group-containing compound and an aldehyde group-containing compound.

[0054] The Schiff base polymer formed by polymerizing the amine-containing compound and the aldehyde-containing compound has a stable carbon-nitrogen double bond (C=N), so that the Schiff base polymer has high thermal stability. The amine-containing compound and the aldehyde-containing compound can be used to obtain the Schiff base polymer through a simple condensation reaction, and the reaction conditions are mild and the reaction efficiency is high.

[0055] In some embodiments, the structural formula of the amine-containing compound is as shown in Formula I to Formula III:

[0056]

[0057] The compounds shown in Formula I to Formula III have multiple amine groups, which can polymerize with aldehyde-containing compounds to form Schiff base polymers, and the exposed amine groups in the formed Schiff base polymers can interact with the cell walls of bacteria, thereby improving the antibacterial performance. Among them, the compound described in Formula I contains phosphorus, which can be decomposed at high temperature to produce phosphorus-containing free radicals and phosphoric acid-containing radical reactions to promote further carbonization of the matrix and interrupt combustion, thereby increasing the flame retardant properties of the material; the compounds shown in Formula II and Formula III contain fluorine, which has a large electronegativity, and its low polarizability can improve the dielectric properties of the polymer system. In addition, the low surface energy of fluorine can also reduce the surface energy of the material, giving the material good hydrophobic properties.

[0058] In some embodiments, the structural formula of the compound containing an aldehyde group is as shown in Formula IV to Formula VI:

[0059]

[0060] The phosphorus element in the compounds shown in Formula IV to Formula VI can be decomposed at high temperature to produce phosphorus-containing free radicals and phosphoric acid-containing free radical reactions that promote further carbonization of the matrix and interrupt combustion, thereby increasing the flame retardant properties of the material. The aldehyde group can react quickly with the compounds shown in Formula I to Formula III to form a Schiff base structure. The reaction is rapid and mild, and is easy to prepare.

[0061] In some embodiments, the carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0062] Both single-walled carbon nanotubes and multi-walled carbon nanotubes have good electrical conductivity, which makes them have excellent electromagnetic wave absorption performance. Among them, single-walled carbon nanotubes have higher strength and toughness, and multi-walled carbon nanotubes have higher mechanical strength than single-walled carbon nanotubes due to the large number of layers. The thermal conductivity of single-walled carbon nanotubes is better than that of multi-walled carbon nanotubes. In practical applications, single-walled carbon nanotubes or multi-walled carbon nanotubes can be reasonably selected according to needs, or single-walled carbon nanotubes and multi-walled carbon nanotubes can be used in combination.

[0063] In some embodiments, the substrate layer includes a fabric layer, and the cover layer covers the fabric layer.

[0064] The fabric layer has good flexibility and strength, and is light and low in cost. By coating the fabric layer with the coating layer, the flame retardancy, antibacterial property and electromagnetic wave absorption property of the fabric layer can be improved. In addition, by arranging the coating layer on the fabric layer, it is also helpful to improve the mechanical strength and thermal conductivity of the fabric layer.

[0065] Exemplarily, the fabric layer includes at least one of a cotton fabric layer, a wool fabric layer, a chemical fiber fabric layer, a blended fabric layer and a non-woven fabric layer. Among them, the cotton fabric layer is preferably used, because the cotton fabric layer has good flexibility and strength, and is light in texture, and is widely used in the decorative layer of the vehicle.

[0066] According to a second aspect of the present application, a method for preparing a decorative layer is also provided, which is used to prepare the decorative layer as described above, comprising:

[0067] Providing multi-level structured carbon nanotube materials;

[0068] Dispersing the multi-level structure carbon nanotube material into the polymer solution to obtain a multi-level structure carbon nanotube material solution;

[0069] The multi-level structure carbon nanotube material solution is coated on the substrate layer and dried to obtain a decorative layer.

[0070] The method for preparing the decorative layer provided in the embodiment of the present application disperses the multi-level structure carbon nanotube material into a pre-cross-linked solution to prepare a composite carbon nanomaterial solution, and then coats the multi-level structure carbon nanotube material solution on a substrate layer, and after drying and curing, forms a composite decorative layer.

[0071] Among them, polymer solution refers to a solution formed by polymer compounds dispersed in a molecular state in a suitable medium. The polymer solution has good processability and formability, which helps it to be coated on other materials to form a stable coating layer. During the processing, it can be evenly covered on the surface of other materials by various methods such as coating, spraying, and dipping. In addition, the molecular weight of the polymer compound in the polymer solution is relatively large, and it has good stability and oxidation resistance. The coating layer formed has the characteristics of oxidation resistance and corrosion resistance, forming a dense barrier.

[0072] In some embodiments, the polymer solution includes at least one of a chitosan solution, a sodium alginate solution, and a polyvinyl alcohol solution.

[0073] In chitosan solution, chitosan is a natural polysaccharide with good biocompatibility and biodegradability, and the cost of chitosan is low. In sodium alginate solution, the molecular structure of sodium alginate is stable, which can improve the stability of the coating layer and has good environmental protection. In polyvinyl alcohol solution, polyvinyl alcohol can effectively protect the substrate layer from the influence of the external environment and enhance the mechanical properties of the substrate layer.

[0074] In some embodiments, the mass proportion of the multi-level structure carbon nanotube material in the multi-level structure carbon nanotube material solution is 5%-30%. By setting the mass proportion of the multi-level structure carbon nanotube material within the above range, it can be ensured that the formed coating layer can provide sufficient flame retardancy, antibacterial and electromagnetic wave absorption performance, while helping the multi-level structure carbon nanotube material to be more evenly dispersed in the multi-level structure carbon nanotube material solution and reduce cost investment. In addition, setting the mass proportion of the multi-level structure carbon nanotube material within the above range can also ensure that the multi-level structure carbon nanotube material solution has a suitable viscosity, so that it has good fluidity, which is convenient for the subsequent coating processing of the substrate layer.

[0075] In some embodiments, the concentration of chitosan in the chitosan solution is 1 mg / mL-20 mg / mL. When the concentration of chitosan in the chitosan solution is set in the above range, it has good film-forming properties, which helps to form a stable coating layer later. And it has a suitable viscosity, which facilitates the uniform dispersion of the multi-level structure carbon nanotube material in the chitosan solution.

[0076] Illustratively, in the chitosan solution, the concentration of chitosan may be 1 mg / mL, 3 mg / mL, 5 mg / mL, 7 mg / mL, 10 mg / mL, 12 mg / mL, 15 mg / mL, 18 mg / mL or 20 mg / mL.

[0077] In some embodiments, the concentration of sodium alginate in the sodium alginate solution is 1 mg / mL-20 mg / mL. The reason why the concentration of sodium alginate in the sodium alginate solution is set in the above range is similar to that of the chitosan solution, which will not be repeated here.

[0078] Illustratively, in the sodium alginate solution, the concentration of sodium alginate can be 1 mg / mL, 3 mg / mL, 5 mg / mL, 7 mg / mL, 10 mg / mL, 12 mg / mL, 15 mg / mL, 18 mg / mL or 20 mg / mL.

[0079] In some embodiments, the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 1 mg / mL-20 mg / mL. The reason why the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is set in the above range is similar to that of the chitosan solution and will not be repeated here.

[0080] Illustratively, in the polyvinyl alcohol solution, the concentration of polyvinyl alcohol may be 1 mg / mL, 3 mg / mL, 5 mg / mL, 7 mg / mL, 10 mg / mL, 12 mg / mL, 15 mg / mL, 18 mg / mL or 20 mg / mL.

[0081] In some embodiments, a method for preparing a multi-level structured carbon nanotube material comprises:

[0082] dispersing carbon nanotubes in a first solvent to obtain a carbon nanotube solution;

[0083] Adding a first solution to the carbon nanotube solution and reacting the solution to obtain a first mixed solution; wherein the first solution includes an amine-containing compound;

[0084] Adding a second solution to the first mixed solution and reacting the solution to obtain a second mixed solution; wherein the second solution includes a compound containing an aldehyde group;

[0085] performing solid-liquid separation on the second mixed solution to obtain coated carbon nanotubes, and redispersing the coated carbon nanotubes in a second solvent to obtain a coated carbon nanotube solution;

[0086] adding a silver nitrate solution to the coated carbon nanotube solution to obtain a third mixed solution;

[0087] Adding a reducing agent solution to the third mixed solution and reacting the solution to obtain a fourth mixed solution;

[0088] The fourth mixed solution is subjected to solid-liquid separation and dried to obtain a multi-level structure carbon nanotube material.

[0089] In the preparation method of the multi-level structure carbon nanotube provided in the embodiment of the present application, the first solution is first mixed with the carbon nanotube solution to form a first mixed solution, so that the amine-containing compound is bonded to the surface of the carbon nanotube through surface hydrogen bonds, which helps the subsequent assembly reaction to be carried out on the surface of the carbon nanotube, thereby forming a dense polymer layer on the surface of the carbon nanotube. Then the second solution is added to the first mixed solution, so that the aldehyde-containing compound and the amine-containing compound are polymerized on the surface of the carbon nanotube through a condensation reaction to form a Schiff base polymer layer to obtain a coated carbon nanotube. After solid-liquid separation, it is re-prepared into a coated carbon nanotube solution, and a silver nitrate solution is added to combine with silver ions by using the reaction sites present in the Schiff base polymer layer, and then the silver ions are reduced in situ by a reducing agent solution to form silver particles on the surface of the Schiff base polymer layer to obtain a multi-level structure carbon nanotube material with a multi-level structure.

[0090] In some embodiments, the concentration of carbon nanotubes in the carbon nanotube solution is 0.1 mg / mL-20 mg / mL.

[0091] By setting the concentration of carbon nanotubes within the above range, it is possible to ensure that the carbon nanotubes are dispersed more evenly, reduce the agglomeration of carbon nanotubes, and thus improve the coating efficiency and effect. The spacing between carbon nanotubes in the carbon nanotube solution is moderate, which helps to form a coating layer of appropriate thickness on the surface of the carbon nanotubes during the subsequent coating reaction, thereby improving the uniformity of the coating.

[0092] Illustratively, in the carbon nanotube solution, the concentration of the carbon nanotubes can be 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 3 mg / mL, 5 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL, 15 mg / mL, 18 mg / mL or 20 mg / mL.

[0093] In some embodiments, the concentration of the amine-containing compound in the first solution is 1 mg / mL-20 mg / mL.

[0094] By setting the concentration of the amine-containing compound within the above range, the amine-containing compound is helped to bind to the surface of the carbon nanotube through surface hydrogen bonding, thereby forming a uniform coating layer in the subsequent process, avoiding problems such as sparse distribution caused by too low concentration or uneven accumulation caused by too high concentration. A reasonable concentration range also helps to form a suitable coating layer thickness, thereby improving the performance of the coated multi-level structure carbon nanotube material.

[0095] In some embodiments, the concentration of the aldehyde-containing compound in the second solution is 1 mg / mL-20 mg / mL.

[0096] Similarly, by setting the concentration of the aldehyde-containing compound within the above range, the aldehyde-containing compound and the amine-containing compound are facilitated to undergo an assembly reaction to form a Schiff base polymer, thereby forming a uniform coating layer on the surface of the carbon nanotube, thereby avoiding problems such as sparse distribution caused by too low a concentration or uneven accumulation caused by too high a concentration. A reasonable concentration range also helps to form a suitable coating layer thickness, thereby improving the performance of the coated multi-level structure carbon nanotube material.

[0097] In some embodiments, the first solvent includes at least one of ethanol and methanol. Ethanol is a polar solvent, and there is an interaction force between it and the carbon nanotubes, which helps to improve the dispersion uniformity of the carbon nanotubes. Ethanol as a solvent can form a stable carbon nanotube solution and reduce the problems of carbon nanotube agglomeration and precipitation. Methanol has a small surface tension, and it can improve the dispersion effect of carbon nanotubes as a solvent, and it can also ensure the stability of the carbon nanotube solution.

[0098] Specifically, ethanol and methanol can be used as solvents alone, or ethanol and methanol can be mixed in a certain ratio and used.

[0099] In some embodiments, the second solvent includes at least one of ethanol and methanol.

[0100] In some embodiments, the concentration of silver nitrate in the silver nitrate solution is 1 mg / mL-20 mg / mL. The concentration of nitric acid in the silver nitrate solution is set within the above range, which can make the anions have a higher reducibility and be easily reduced by the reducing agent to form nano-scale silver particles, and also help the silver nitrate to be more evenly dispersed, thereby forming silver particles with uniform particle size after in-situ reduction, and it is not easy to cause problems such as oxidation or agglomeration during the reaction process.

[0101] In some embodiments, the reducing agent solution includes at least one of a sodium borohydride solution and a sodium citrate solution. Among them, sodium borohydride is a strong reducing agent that can reduce silver ions to metallic silver, and the reaction conditions are mild and easy to control. Compared with sodium borohydride, sodium citrate has weaker reducing properties and milder reaction conditions. Through reduction with sodium borohydride or sodium citrate, silver nanoparticles with narrow particle size distribution and uniform shape can be generated, thereby improving reaction stability.

[0102] According to the third aspect of the present application, there is also provided an automotive interior decoration part, comprising the decorative layer as described above, and / or the decorative layer prepared by the method for preparing the decorative layer as described above. The automotive interior decoration part provided in the embodiment of the present application has all the beneficial effects of the decorative layer as described above, which will not be repeated here.

[0103] According to a fourth aspect of the present application, a vehicle is also provided, comprising the above-mentioned automobile interior decoration part. The vehicle provided by the embodiment of the present application has all the beneficial effects of the above-mentioned decorative layer, which will not be repeated here.

[0104] The following examples are further described in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on the conditions recommended by the manufacturer.

[0105] Example 1

[0106] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0107] (2) adding 10 mL of the first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is the compound represented by formula I;

[0108]

[0109] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0110]

[0111] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0112] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0113] (6) adding 10 mL of a 1 mg / mL sodium borohydride solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0114] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0115] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0116] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0117] Example 2

[0118] (1) ultrasonically dispersing 10 mg of multi-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0119] (2) adding 10 mL of a first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0120]

[0121] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0122]

[0123] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0124] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0125] (6) adding 10 mL of a 1 mg / mL sodium borohydride solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0126] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0127] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0128] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0129] Example 3

[0130] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0131] (2) adding 10 mL of the first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 hours to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula II;

[0132]

[0133] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula V;

[0134]

[0135] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0136] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0137] (6) adding 10 mL of a 1 mg / mL sodium borohydride solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0138] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0139] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0140] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0141] Example 4

[0142] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0143] (2) adding 10 mL of the first solution having a concentration of 1 mg / mL into the carbon nanotube solution, and stirring at room temperature for 2 hours to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula III;

[0144]

[0145] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula VI;

[0146]

[0147] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0148] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0149] (6) adding 10 mL of a 1 mg / mL sodium borohydride solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0150] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0151] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0152] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0153] Example 5

[0154] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0155] (2) adding 10 mL of a first solution having a concentration of 2 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0156]

[0157] (3) adding a second solution having a concentration of 2 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0158]

[0159] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0160] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0161] (6) adding 10 mL of a 1 mg / mL sodium borohydride solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0162] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0163] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0164] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0165] Example 6

[0166] (1) ultrasonically dispersing 20 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0167] (2) adding 10 mL of a first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0168]

[0169] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0170]

[0171] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0172] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous methanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0173] (6) adding 10 mL of a 1 mg / mL sodium borohydride solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0174] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0175] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0176] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0177] Example 7

[0178] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous methanol to obtain a carbon nanotube solution;

[0179] (2) adding 10 mL of a first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0180]

[0181] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0182]

[0183] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous methanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous methanol to obtain a coated carbon nanotube solution;

[0184] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous methanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0185] (6) adding 10 mL of a 1 mg / mL sodium borohydride solution (solvent: anhydrous methanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0186] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous methanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0187] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0188] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0189] Example 8

[0190] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0191] (2) adding 10 mL of a first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0192]

[0193] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0194]

[0195] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0196] (5) adding 10 mL of a 2 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0197] (6) adding 10 mL of a 1 mg / mL sodium borohydride solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0198] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0199] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0200] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0201] Example 9

[0202] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0203] (2) adding 10 mL of a first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0204]

[0205] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0206]

[0207] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0208] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0209] (6) adding 10 mL of a 2 mg / mL sodium borohydride solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0210] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0211] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0212] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0213] Example 10

[0214] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0215] (2) adding 10 mL of a first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0216]

[0217] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0218]

[0219] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0220] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0221] (6) adding 10 mL of a 1 mg / mL sodium citrate solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0222] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0223] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0224] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0225] Embodiment 11

[0226] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0227] (2) adding 10 mL of a first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0228]

[0229] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0230]

[0231] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0232] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0233] (6) adding 10 mL of a 1 mg / mL sodium citrate solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0234] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0235] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a sodium alginate solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0236] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0237] Example 12

[0238] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0239] (2) adding 10 mL of a first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0240]

[0241] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0242]

[0243] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0244] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0245] (6) adding 10 mL of a 1 mg / mL sodium citrate solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0246] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0247] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a polyvinyl alcohol solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 10%;

[0248] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0249] Embodiment 13

[0250] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0251] (2) adding 10 mL of a first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0252]

[0253] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0254]

[0255] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0256] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0257] (6) adding 10 mL of a 1 mg / mL sodium citrate solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0258] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0259] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 5%;

[0260] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0261] Embodiment 14

[0262] (1) ultrasonically dispersing 10 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0263] (2) adding 10 mL of a first solution having a concentration of 1 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 h, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0264]

[0265] (3) adding a second solution having a concentration of 1 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0266]

[0267] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0268] (5) adding 10 mL of a 1 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0269] (6) adding 10 mL of a 1 mg / mL sodium citrate solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0270] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0271] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 1 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 20%;

[0272] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0273] Embodiment 15

[0274] (1) ultrasonically dispersing 500 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0275] (2) adding 10 mL of a first solution having a concentration of 20 mg / mL into the carbon nanotube solution, and stirring at room temperature for 2 hours to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0276]

[0277] (3) adding 10 mL of the second solution having a concentration of 20 mg / mL to the first mixed solution, and stirring at room temperature for 2 h to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0278]

[0279] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0280] (5) adding 10 mL of a 20 mg / mL silver nitrate solution (solvent: anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0281] (6) adding 10 mL of a 20 mg / mL sodium borohydride solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0282] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0283] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 20 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 15%;

[0284] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0285] Example 16

[0286] (1) ultrasonically dispersing 1000 mg of single-walled carbon nanotubes in 50 mL of anhydrous ethanol to obtain a carbon nanotube solution;

[0287] (2) adding 10 mL of a first solution having a concentration of 10 mg / mL into the carbon nanotube solution, stirring at room temperature for 2 hours, to obtain a first mixed solution; wherein the first monomer in the first solution is a compound represented by formula I;

[0288]

[0289] (3) adding 10 mL of the second solution having a concentration of 10 mg / mL to the first mixed solution, and stirring at room temperature for 2 hours to obtain a second mixed solution; wherein the second monomer in the second solution is a compound represented by formula IV;

[0290]

[0291] (4) performing solid-liquid separation on the second mixed solution, washing twice with anhydrous ethanol to coat the carbon nanotubes, and then redispersing the coated carbon nanotubes in 50 mL of anhydrous ethanol to obtain a coated carbon nanotube solution;

[0292] (5) adding 10 mL of a 10 mg / mL silver nitrate solution (the solvent is anhydrous ethanol) to the coated carbon nanotube solution, and reacting at room temperature for 2 h to obtain a third mixed solution;

[0293] (6) adding 10 mL of a 10 mg / mL sodium borohydride solution (solvent: anhydrous ethanol) to the third mixed solution, reacting at room temperature for 2 h to obtain a fourth mixed solution;

[0294] (7) separating the fourth mixed solution into solid and liquid, washing it twice with anhydrous ethanol, and drying it to obtain a multi-level structure carbon nanotube material;

[0295] (8) dispersing the multi-level structure carbon nanotube material into 100 mL of a chitosan solution having a concentration of 10 mg / mL to obtain a multi-level structure carbon nanotube material solution having a mass concentration of 30%;

[0296] (9) Immersing the cotton fabric layer in the multi-level structure carbon nanotube material solution for 20 minutes, taking it out and drying it at 70° C. to obtain a decorative layer.

[0297] Comparative Example 1

[0298] The cotton fabric layer was immersed in a chitosan solution with a concentration of 1 mg / mL, taken out and dried at 70° C. to obtain a decorative layer.

[0299] Comparative Example 2

[0300] The cotton fabric layer was immersed in an alginate solution with a concentration of 1 mg / mL, taken out and dried at 70° C. to obtain a decorative layer.

[0301] Comparative Example 3

[0302] The cotton fabric layer was immersed in a polyvinyl alcohol solution with a concentration of 1 mg / mL, taken out and dried at 70° C. to obtain a decorative layer.

[0303] The XRD (X-ray diffraction) spectrum of the multi-level structure carbon nanotube material obtained in Example 1 was tested and compared with the XRD spectrum of the carbon nanotube. Figure 1 As shown in FIG. 1 , CNT@PP@AgNP represents the multi-level structure carbon nanotube material prepared in Example 1, and CNT represents carbon nanotube. Figure 1It can be seen that, relative to carbon nanotubes (CNTs), the multi-level structure carbon nanotube material (CNT@PP@AgNP) prepared in Example 1 has characteristic peaks of Schiff base polymer and silver particles in addition to the characteristics of carbon nanotubes, indicating that the multi-level structure nanotube material in Example 1 has carbon nanotubes, Schiff base polymer and silver particles at the same time.

[0304] The carbon nanotubes in Example 2 and the obtained multi-level structure carbon nanotube material were analyzed by TEM (transmission electron microscope).

[0305] like Figure 2 As shown, Figure 2 (A) is a TEM image of carbon nanotubes. Figure 2 (B) is a TEM image of carbon nanotubes coated with Schiff base polymers. Figure 2 (C) is a TEM image of a multi-level structured carbon nanotube material. Figure 2 As can be seen in (B), after the introduction of the Schiff base polymer, a layer of polymer can be found to grow on the surface of the carbon nanotube; Figure 2 As can be seen in (C), the reduced metal particles can also be clearly found on the chemically reduced carbon nanotubes. Figure 2 As can be seen from (D)-(F), the metal particles on the hierarchical carbon nanotube material are silver. These results uniformly illustrate the successful preparation of the hierarchical carbon nanotube material.

[0306] The antibacterial property, flame retardant property, thermal conductivity, tensile property and electromagnetic wave absorption property of the decorative layer in Examples 1-16 and Comparative Example 1 were tested. The antibacterial property was tested according to the method specified in GB / T 20944.3-2008; the flame retardant property was tested by vertical combustion (UL-94) according to the method specified in ASTM-D 3801; the thermal conductivity was tested according to the thermal conductivity test method specified in ASTM-E1461; and the tensile property was tested according to the method specified in GB / T 3929.2-2003.

[0307] The electromagnetic wave absorption performance is tested by the coaxial line method: 40wt% of the test sample (decorative layer in Examples 1-16 and Comparative Example 1) is mixed with 40wt% of paraffin wax and pressed into a coaxial ring with an outer diameter of 7.0mm, an inner diameter of 3.04mm, and a thickness of 2.0mm for electromagnetic parameter testing. The test instrument model is Agilent's PNA N5224A. The electromagnetic wave absorption performance is evaluated by the reflection loss value (RL), which is calculated according to the transmission line theory, as shown in Formula 1 and Formula 2:

[0308] Z in =Z0(μ r / ε r)1 / 2tanh[j(2πfd / c)(μ r ε r )]1 / 2 formula 1;

[0309] RL=20log10|(Z in -Z0) / (Z in +Z0)| Formula 2;

[0310] Among them, Z0 and Z in Represent free space impedance and standard input impedance respectively; ε r =ε'-jε", ε' and ε" correspond to the real and imaginary parts of the dielectric constant, respectively; μr = μ'-jμ", μ' and μ" correspond to the real and imaginary parts of the magnetic permeability, respectively; f is the microwave frequency; d is the sample thickness; c is the speed of light.

[0311] The test results are shown in Table 1:

[0312] Table 1 Performance test results of the decorative layer in Examples 1-16 and Comparative Example 1

[0313]

[0314]

[0315] As can be seen from Table 1, the antibacterial performance, tensile strength, thermal conductivity, electromagnetic wave absorption performance and flame retardant performance of the decorative layer obtained in the embodiment of the present application are improved to varying degrees compared with the decorative layer obtained in Comparative Example 1, indicating that the decorative layer provided in the embodiment of the present application can significantly improve the comprehensive performance of the decorative layer by providing a coating layer of a multi-level structured carbon nanotube material, and while ensuring lightweight and mechanical properties, the decorative layer is used to achieve functions such as electromagnetic wave absorption, flame retardancy, antibacterial, and thermal conductivity.

[0316] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0317] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0318] The embodiments, implementation methods and related technical features of the present application can be combined and replaced with each other without conflict.

[0319] The above are only preferred embodiments of the present application and do not constitute any form of limitation to the present application. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A decorative layer, applied to a vehicle, characterized in that: include: substrate layer; A coating layer, wherein the coating layer covers the substrate layer; The coating layer comprises a multi-level structure carbon nanotube material, which comprises carbon nanotubes, a Schiff base polymer layer coated on the surface of the carbon nanotubes, and metal particles supported on the Schiff base polymer layer.

2. The decorative layer according to claim 1, characterized in that: The metal particles include silver particles.

3. The decorative layer according to claim 1, characterized in that: The Schiff base polymer in the Schiff base polymer layer is formed by polymerizing an amine group-containing compound and an aldehyde group-containing compound.

4. The decorative layer according to claim 3, characterized in that: The structural formula of the amine-containing compound is shown in Formula I to Formula III:

5. The decorative layer according to claim 4, characterized in that: The structural formula of the aldehyde-containing compound is shown in Formula IV to Formula VI:

6. The decorative layer according to any one of claims 1 to 5, characterized in that: The carbon nanotubes include at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.

7. The decorative layer according to any one of claims 1 to 5, characterized in that: The base material layer includes a fabric layer, and the covering layer covers the fabric layer.

8. A method for preparing a decorative layer, for preparing the decorative layer according to any one of claims 1 to 7, characterized in that: include: Providing multi-level structured carbon nanotube materials; Dispersing the multi-level structure carbon nanotube material into a polymer solution to obtain a multi-level structure carbon nanotube material solution; The multi-level structure carbon nanotube material solution is coated on the substrate layer and dried to obtain a decorative layer.

9. The method for preparing the decorative layer according to claim 8, characterized in that: The polymer solution includes at least one of a chitosan solution, a sodium alginate solution and a polyvinyl alcohol solution.

10. The method for preparing the decorative layer according to claim 9, characterized in that: The mass proportion of the multi-level structure carbon nanotube material in the multi-level structure carbon nanotube material solution is 5%-30%.

11. The method for preparing the decorative layer according to claim 9, characterized in that: The concentration of chitosan in the chitosan solution is 1 mg / mL-20 mg / mL; And / or, the concentration of sodium alginate in the sodium alginate solution is 1 mg / mL-20 mg / mL; And / or, the concentration of polyvinyl alcohol in the polyvinyl alcohol solution is 1 mg / mL-20 mg / mL.

12. The method for preparing the decorative layer according to claim 8, characterized in that: The method for preparing the multi-level structure carbon nanotube material comprises: dispersing carbon nanotubes in a first solvent to obtain a carbon nanotube solution; Adding a first solution to the carbon nanotube solution and reacting the solution to obtain a first mixed solution; wherein the first solution includes an amine-containing compound; Adding a second solution to the first mixed solution and reacting the solution to obtain a second mixed solution; wherein the second solution includes a compound containing an aldehyde group; performing solid-liquid separation on the second mixed solution to obtain coated carbon nanotubes, and redispersing the coated carbon nanotubes in a second solvent to obtain a coated carbon nanotube solution; adding a silver nitrate solution to the coated carbon nanotube solution to obtain a third mixed solution; Adding a reducing agent solution to the third mixed solution and reacting to obtain a fourth mixed solution; The fourth mixed solution is subjected to solid-liquid separation and dried to obtain the multi-level structure carbon nanotube material.

13. The method for preparing the decorative layer according to claim 12, characterized in that: In the carbon nanotube solution, the concentration of the carbon nanotubes is 0.1 mg / mL-20 mg / mL; and / or, in the first solution, the concentration of the amine-containing compound is 1 mg / mL-20 mg / mL; And / or, in the second solution, the concentration of the aldehyde-containing compound is 1 mg / mL-20 mg / mL.

14. The method for preparing a decorative layer according to claim 12, characterized in that: The first solvent includes at least one of ethanol and methanol; And / or, the second solvent includes at least one of ethanol and methanol.

15. The method for preparing a decorative layer according to claim 12, characterized in that: In the silver nitrate solution, the concentration of silver nitrate is 1 mg / mL-20 mg / mL.

16. The method for preparing a decorative layer according to claim 12, characterized in that: The reducing agent solution includes at least one of a sodium borohydride solution and a sodium citrate solution.

17. An automotive interior component, characterized in that: The invention comprises the decorative layer as claimed in any one of claims 1 to 7, and / or the decorative layer prepared by the method for preparing the decorative layer as claimed in any one of claims 8 to 16.

18. A vehicle, characterized in that: Comprising the automotive interior trim component as claimed in claim 17.